1931
DOI: 10.1042/bj0250643
|View full text |Cite
|
Sign up to set email alerts
|

The influence of calcium on the rate of diffusion of sugars through surviving intestine

Abstract: IN previous work on this subject [Macleod et al. 1930; Auchinachie et al. 1930], the fluid bathing the surviving segments of intestine was always sugar-free Tyrode's solution. In view of the well-known effects of electrolytes on the physiological activity of living cells, it was decided to determine whether the selective properties of the intestinal epithelial cells would be affected by varying the composition of the outer fluid. The procedure was the same as in previous experiments except that, as it was nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1932
1932
1961
1961

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…
WE have shown that the selective action exerted by the epithelium of surviving intestine on sugar solutions placed in the lumen depends on the presence of Ca ions in the bathing fluid, so that when segments were immersed in Ca-free Tyrode the sugars passed through the intestinal wall in accordance with physical laws [Magee and Sen, 1931]. The present experiments were undertaken as an extension of this work, the objective being to determine whether the rate of absorption of glucose is related in any way to the level of Ca in the blood of the living animal.
…”
mentioning
confidence: 99%
“…
WE have shown that the selective action exerted by the epithelium of surviving intestine on sugar solutions placed in the lumen depends on the presence of Ca ions in the bathing fluid, so that when segments were immersed in Ca-free Tyrode the sugars passed through the intestinal wall in accordance with physical laws [Magee and Sen, 1931]. The present experiments were undertaken as an extension of this work, the objective being to determine whether the rate of absorption of glucose is related in any way to the level of Ca in the blood of the living animal.
…”
mentioning
confidence: 99%
“…It was therefore of interest to study the influence of calcium on the permeability of the intestine. Magee and Sen [1931] showed that the selective permeability of the surviving intestine for glucose requires the presence of calcium ions in the bathing fluid. When the segments were immersed in Ca-free Tyrode, glucose passed out more slowly than xylose; whereas in the presence of calcium, glucose passed out more quickly than xylose.…”
mentioning
confidence: 99%